Η εκλογή και η επίσημη είσοδος του λατίνου επισκόπου Paolo da Ponte (1765) στην Αρχιεπισκοπή της Κέρκυρας - Γαούτσης Σπύρος Π. (Peri Istorias, 2022)
The election and official entry of the Latin Bishop Paolo Da Ponte (1765) in the Archdiocese of Corfu The destruction of the old archive of the Catholic Archdiocese of Corfu in September 1943 caused a great loss and a gap in the sources concerning the establishment and the missionary activity of the Catholic archbishops during the Venetian period and beyond. In this paper there is an effort to describe the personality of the (Latin) Archbishop of Corfu in the period between 1765-1773, so there will be further study of F. 95 of the series "Venetian rule" from the Corfu Archives, as well as newer anecdotal data, capturing the arrival of the Venetian Paolo Da Ponte, member of the religious order of the Discalced Carmelites and the peculiar civil ritual used to mark the official establishment, the powers, but also the "divine mission" he undertook, in his new position.